Decision Making and Organisation in the Decision Making Process from Andreas Faludi's perspective - Izzah, Ikfina Nurul; Suyatman, Ujang (AIM: Journal of Islamic Education Management, 2024)
This theme explores the complexity of decision-making and organizational structure in planning agencies. Decision-making in planning agencies requires a balance between a rational approach based on data and analysis, and a participatory approach that accommodates various social, economic, and political interests. Meanwhile, the organization of planning departments needs a clear structure to ensure well-distributed roles and responsibilities, enabling effective coordination both internally and externally. Additionally, planning agencies often face political pressures that influence processes and outcomes. Therefore, the ability to adapt to political interests while maintaining the integrity of the plan is a primary challenge. A balance between technical rationality and flexibility in addressing diverse interests is key to successful decision-making and to the effectiveness of organizational structure in responsive and sustainable planning.